2019
DOI: 10.1111/ijcp.13422
|View full text |Cite
|
Sign up to set email alerts
|

Extended‐spectrum beta‐lactamase (ESBL)‐producingEnterobacteriaceaeand urinary tract infections in pregnant/postpartum women: A systematic review and meta‐analysis

Abstract: Background Urinary tract infections (UTI) and asymptomatic bacteriuria (AB) during pregnancy can result in considerable maternal and foetal adverse outcomes. Production of extended‐spectrum beta‐lactamase (ESBL) is a major antibiotic resistance mechanism by Enterobacteriaceae. Objectives To determine the global prevalence of ESBL‐producing (ESBL‐P) Enterobacteriaceae in symptomatic UTI/AB among pregnant/postpartum females. Data sources A systematic review of the PubMed, Embase, Scopus, WOS (Web of Science), Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 51 publications
(142 reference statements)
2
18
3
2
Order By: Relevance
“…In the present study, the prevalence of vaginal Enterobacterales and ESBL-Enterobacterales colonization among pregnant women was 30% and 10%, respectively. The ESBL-E incidence observed in this study is higher than other upper-middle-income countries, such as Norway (3%) [15] and Argentina (5%) [17], but lower than in other African countries (17%), respectively [18]. Nonuniform approaches to study design, particularly differences in inclusion criteria, age groups, the inclusion of hospital and/or community populations, etc., may modulate the reported ESBL incidences across geographic regions [19].…”
Section: Discussioncontrasting
confidence: 56%
“…In the present study, the prevalence of vaginal Enterobacterales and ESBL-Enterobacterales colonization among pregnant women was 30% and 10%, respectively. The ESBL-E incidence observed in this study is higher than other upper-middle-income countries, such as Norway (3%) [15] and Argentina (5%) [17], but lower than in other African countries (17%), respectively [18]. Nonuniform approaches to study design, particularly differences in inclusion criteria, age groups, the inclusion of hospital and/or community populations, etc., may modulate the reported ESBL incidences across geographic regions [19].…”
Section: Discussioncontrasting
confidence: 56%
“…The estimated prevalence of Enterobacteriaceae in these two studies was slightly higher than the estimated prevalence of nosocomial MDR K. pneumoniae in this analysis. Another study by Mansouri et al [ 55 ] showed a pooled prevalence of ESBL-producing Enterobacteriaceae at 25% (95% CI, 18.0–32.0) globally. In addition, the recorded estimated prevalence in Africa, Asia, Europe, South America, and North America was 45% (95% CI, 22.0–67.0), 15% (95% CI, 6.0–24.0), 5% (95% CI, 2.0–8.0), 4% (95% CI, 1.0–11.0), and 3% (95% CI, 1.0–5.0), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…As compared to resource-rich countries, the pooled proportion of ESBL-producing isolates was thus considerably higher in resource-limited countries, including our setting. For instance, the pooled global prevalence of ESBL‐producing Enterobacteriaceae among pregnant women diagnosed with urinary tract infections (UTIs) is 25%, with the highest rates in Africa (45%) and India (33%), followed by 15% in other Asian countries, 5% (2.8%) in Europe and the lowest one of 4% in South America and 3% in North America ( 37 ). This study finding is also close to data reported for China, where a nationwide survey that included 30 hospitals reported over 46% resistance due to ESBL ( 38 ).…”
Section: Discussionmentioning
confidence: 99%